Primary Prevention of Cardiovascular Disease at Community Clinics in the State of Sao Paulo, Brazil: Results from the Epidemiological Information Study of Communities - Henrique Andrade R. Fonseca; Maria Cristina O. Izar; Luciano F. Drager; Ibraim M. Pinto; José Francisco K. Saraiva; João Fernando Monteiro Ferreira; Álvaro Avezum; Francisco Antonio Fonseca; Otávio Berwanger (Global Heart, 2023)
Background: Primary prevention of cardiovascular disease (CVD) remains a major challenge, especially in communities of low- and middle-income countries with poor medical assistance influenced by distinct local, financial, infrastructural, and resource-related factors. Objective: This a community-based study aimed to determine the proportion and prevalence of uncontrolled cardiovascular risk factors (CRF) in Brazilian communities. Methods: The EPICO study was an observational, cross-sectional, and community clinic-based study. Subjects were living in Brazilian communities and were of both sexes and ≥18 years old, without a history of a stroke or myocardial infarction but presenting at least one of the following cardiovascular risk factors: hypertension, diabetes mellitus and hypercholesterolemia. The study was carried out in Brazil, including 322 basic health units (BHU) in 32 cities. Results: A total of 7,724 subjects with at least one CRF were evaluated, and one clinical visit was performed. Mean age was 59.2 years-old (53.7% were >60 years old). A total of 66.7% were women. Of the total, 96.2% had hypertension, 78.8% had diabetes mellitus type II, 71.1% had dyslipidemia, and 76.6% of patients were overweight/obese. Controlled hypertension (defined by <130/80 mmHg or <140/90 mmHg) was observed in 34.9% and 55.5% patients among respective criteria, the rates of controlled blood glucose in patients taking antidiabetic medications was 29.5%, and among those with documented dyslipidemia who received any lipid-lowering medication, only 13.9% had LDL-c on target. For patients presenting three CRF less than 1.9% had LDL-c < 100 mg/dL once their BP and blood glucose were on target. High education level as associated with blood pressure (BP) target of less than 130 / 80mm Hg. The glucose and LDL-c levels on target were associated with the presence of hypertension and diabetes mellitus. Conclusion: In Brazilian community clinics, regarding most patients in primary prevention, the CRF such as BP, blood glucose, and lipid levels are poorly controlled, with a majority of patients not achieving guidelines/recommendations.